PENGARUH PENERAPAN REGISTRASI ULANG PENGUSAHA KENA PAJAK TERHADAP KEPATUHAN WAJIB PAJAK (Studi Terhadap Pengusaha Kena Pajak pada Kantor Pelayanan Pajak Pratama Singosari) - Nugraha, Fafan Yuda (Jurnal Mahasiswa Perpajakan, 2014)
This research was backed by the efforts of modernisation of the taxation of carried out by the Directorate General of Taxation ( DJP ) , where in 2012 the DJP sector reform VAT administration to curb the Taxable Person ( PKP ) which has been confirmed through the implementation of PKP Re- Registration program. This study aimed to clarify the effect of variable Service Improvement ( X1 ) , Control Administration ( X2 ) , and Control ( X3 ) simultaneously and partially on Taxpayer Compliance ( Y ) . The method used in this research is explanatory research method , using a questionnaire as a data collection tool that is distributed to 68 registered in STO PFM Singosari . Analysis of the data in this study using descriptive analysis and multiple linear regression analysis aided by SPSS software version 16 .The results of multiple linear regression analysis showed that the variable Service Improvement ( X1 ) , Control Administration ( X2 ) , and Control ( X3 ) has a significant influence on simultaneously and Taxpayer Compliance ( Y ) . Keywords : Re- Registration program , Service Improvement, Control Administration , Control, Taxpayer Compliance